2020
DOI: 10.1016/j.clcc.2020.05.011
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the Global Impact on Colorectal Practice and Surgery

Abstract: We have presented the results of a survey used to assess the global impact of coronavirus disease 2019 (COVID-19) on the delivery of colorectal surgery. Despite accessible guidance information, our results have demonstrated that COVID-19 has significantly affected the ability of colorectal surgeons to offer care to patients. We have also discussed practical adaptation strategies for use during the recovery phase. Background: The novel severe acute respiratory syndrome coronavirus 2 virus that emerged in Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 57 publications
0
43
0
Order By: Relevance
“…Nunoo-Mensah et al conducted a survey concerning the global effects of COVID-19 on colorectal practice and surgery, and they reported that COVID-19 has affected the ability of colorectal surgeons to offer care to their patients. They demonstrated that 61% of the surgeons were prepared to defer the elective surgeries for CRCs, with 29% willing to defer for ≤8 weeks [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nunoo-Mensah et al conducted a survey concerning the global effects of COVID-19 on colorectal practice and surgery, and they reported that COVID-19 has affected the ability of colorectal surgeons to offer care to their patients. They demonstrated that 61% of the surgeons were prepared to defer the elective surgeries for CRCs, with 29% willing to defer for ≤8 weeks [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 , 5 The impact of COVID-19 on global oncological care has been profound. 6 , 7 , 8 COVIDSurg Collaborative estimated that 28,404,603 elective operations were cancelled or postponed worldwide during the 12 weeks of peak disruption, with 38% being for cancer. 4 Colorectal cancer (CRC) is the third leading cause of cancer related deaths globally.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there may be a longer holdback for rescheduling once the moratorium is lifted [16]. Currently there are several suggestions for various practical adaptation strategies for use during infection and recovery period [17]. Cancer patients receiving anticancer regimen have been generally believed at a higher risk of COVID-19 infection than those patients who are not receiving anticancer treatment [18].…”
Section: Introductionmentioning
confidence: 99%